International Legal Norms as a Source of Criminal Procedural Law - KHOVPUN, Oleksii S.; ZAVYDNIAK, Volodymyr I.; ZAVYDNIAK, Iryna O.; KOVTUN, Valentina M.; ZHURAVEL, Yaroslav V. (Journal of Advanced Research in Law and Economics; Vol 10 No 5 (2019): JARLE Volume X Issue 5(43) Fall 2019, 2019)
According to a number of indicators, criminal procedural law is considered as an aspect of the exercise of rights and procedures for applying to various judicial instances. However, this position is true, provided that each aspect of the administration of justice is determined primarily by a set of certain knowledge and phenomena that determine the adequacy of the trial. The novelty of the study is determined by the fact that international sources of criminal procedural law are understood primarily not only as the process of investigation of the crime. The authors consider, as a possible application of the norms of international procedural law, such forms as provisions of the legislation on the development of the judicial system, the formation of an equal court and, accordingly, punishment in different legal systems in terms of structure and principles of implementation. The article shows the possibility of implementing general legal norms that form the modern criminal procedural law. The authors note that such an opportunity can be realized with the assistance of various states to the common tasks of developing the legal system. The practical application of the study is possible provided that the applicable rules in international law take precedence over national law, which in turn forms the practice of applying law in a broad form of implementation.